The clinical significance of neutrophilic pleocytosis in cerebrospinal fluid in patients with viral central nervous system infections. (June 2017) - Jaijakul, Siraya; Salazar, Lucrecia; Wootton, Susan H.; Aguilera, Elizabeth; Hasbun, Rodrigo
Highlights: Viral central nervous system (CNS) infections can present with neutrophilic pleocytosis in the cerebrospinal fluid (CSF), but its clinical significance remains unknown. CSF neutrophilic pleocytosis is most commonly seen in younger patients with enterovirus CNS infections. CSF neutrophilic pleocytosis was found not to be associated with higher adverse clinical outcomes in this study. Summary: Background: Viral central nervous system (CNS) infections are typically characterized by a cerebrospinal fluid (CSF) lymphocytic pleocytosis. A CSF neutrophilic pleocytosis presentation has been described, but its prognostic and clinical significance is unknown. The objectives of this study were to (1) compare the clinical and laboratory characteristics of viral CNS infections with a CSF neutrophilic pleocytosis to those with a lymphocytic pleocytosis, and (2) evaluate factors associated with an adverse clinical outcome. Methods: A retrospective study of patients with confirmed viral CNS infections was conducted. The patients were divided into those with CSF neutrophilic pleocytosis and those with CSF lymphocytic pleocytosis. Clinical findings and outcomes were compared between the two groups. Results: Of the 182 patients included in the study, 45 (24.7%) had CSF neutrophilic pleocytosis. Enterovirus infections were the cause of 64% of neutrophil-predominant CSF and 33% of lymphocyte-predominant CSF ( p < 0.001), while herpes infections were the cause of 46% of lymphocytic pleocytosis and 20% of neutrophilic pleocytosis ( p = 0.003). Moreover, neutrophilic pleocytosis was seen more commonly in younger patients ( p = 0.001), patients with respiratory symptoms ( p = 0.04), and patients with higher CSF white cell counts ( p = 0.004). Twenty-nine patients had an adverse clinical outcome (15.9%); the only predictor independently associated with an adverse clinical outcome on multivariable logistic regression analysis was an encephalitis presentation ( p = 0.01). Conclusions: The results of a study exploring the association between CSF neutrophilic pleocytosis and clinical and prognostic significance are presented here. This study suggests that CSF neutrophilic pleocytosis is not associated with higher adverse clinical outcomes.